The Poetry of Ibn Baqī al-Andalusī: A Study in the Light of Reception Theory - علوش, زينب علي صادق جواد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Literary criticism witnessed in its course the emergence of new critical approaches, whose trends differed in terms of focusing on one of the axes of the literary work (the author, the text, the recipient) without the other two poles. The interest in the author was in light of the contextual approaches, which glorified the external factors and made them the reference and destination in the literary work, and the systemic approaches came and focused on the text itself and made it the focus of the creative process. These two trends neglected the third axis of the creative process, which is the recipient of the literary work. The function of a literary text cannot be completed without the process of reception. Although the creator of this text - whether a poet or a prose writer - can produce his text freed from a specific and tangible presence of the recipient, the creator cannot get rid of the domination of this recipient over him. From here came theories that focused on (the recipient) in an attempt to highlight the fundamental role that he plays in the process of constructing meaning. The most prominent of these theories is the “Reception Theory” in its German edition by “Hans Robert Jauss” and “Wolfgang Iser.”